How to Avoid Multiple Gestations Following ART? - Kovacs, Peter; Kaali, Steven G. (Current Women's Health Reviews, 2006)
The rate of multiple gestations has increased dramatically over the past three decades. Most of the excess multiple pregnancies are due to the widespread use of ART. Nowadays, IVF is responsible for most of the twins, while ovarian stimulation is responsible for most of the higher-order multiples. A multiple gestation, even a twin gestation, is associated with significant maternal and fetal risks. The extra expenses place a burden on the health care system. Many attempts were made to identify patient, stimulation and laboratory characteristics that are associated with better implantation potential. Improvements in laboratory technology (preimplantation genetic screening, extended embryo culture) have also helped to limit the number of embryos transferred. The best approach to reduce the risk of multiple gestations is to limit the number of embryos transferred. Elective single embryo transfer essentially eliminates multiple gestations but is associated with lower pregnancy rates in an unselected group of patients. It is currently recommended to a minority of couples with excellent prognosis. Future research should try to identify other markers (e.g.: embryonic products from culture medium) that could be used to identify those embryos that have the best chance for successful implantation. This review will summarize the efforts made so far to reduce the incidence of multiple gestations.
Keywords: ovulation induction